Anatomy and Connectivity of the Subthalamic Nucleus in Humans and Non-human Primates - Emmi, Aron; Antonini, Angelo; Macchi, Veronica; Porzionato, Andrea; De Caro, Raffaele (Frontiers in Neuroanatomy, 2020)
The Subthalamic Nucleus (STh) is an oval-shaped diencephalic structure located ventrally to the thalamus, playing a fundamental role in the circuitry of the basal ganglia. In addition to being involved in the pathophysiology of several neurodegenerative disorders, such as Huntington’s and Parkinson’s disease, the STh is one of the target nuclei for deep brain stimulation. However, most of the anatomical evidence available derives from non-human primate studies. In this review, we will present the topographical and morphological organization of the nucleus and its connections to structurally and functionally related regions of the basal ganglia circuitry. We will also highlight the importance of additional research in humans focused on validating STh connectivity, cytoarchitectural organization, and its functional subdivision.